Safe play areas on farms in New South Wales. (16th August 2013) - Depczynski, Julie; Herde, Emily; Fragar, Lyn; Lower, Tony
Abstract Objective To assess the prevalence and security of fenced house yards on NSW farms and rural properties with a view to providing information to increase the development of safe play areas on farms. Design A cross‐sectional stratified study using computer‐assisted telephone interviewing. Setting Interviews were conducted in the four rural Area Health Services throughout February to December 2008. Participants Randomly selected sample of 1117 adults living on a farm or rural property in the study areas. Main Outcome Measures Self‐reported issues involving fenced house yards or safe play areas for children. Results Overall, 79.8% of farm respondents reported that they had a fenced house yard or safe play area. For those respondents with a fenced house yard, 66.6% reported that it was secure enough to prevent /make it difficult for a young child to wander away unsupervised. Based on these figures, it is estimated that only 53.1% of all farms or rural properties have a secure fenced house yard or safe play area. There were statistically significant variations between geographic locations, with the North Coast (37.7%) being lower. Conclusions This study illustrates a need across rural NSW to further promote, install or upgrade secure fenced house yards or safe play areas. While all geographic regions of the state could improve provision to protect children, there may also be some that are in need of more intensive intervention programs to enhance compliance. Such a proposition may also be relevant on a national level.